Studying, designing and 3d-printing an operational model of the Antikythera Mechanism - Mavromanolakis, Georgios; Manousos, T; Kechri, M; Kollia, P. L.; Kanellopoulos, G (Open Schools Journal for Open Science, 2019)
3D printing technology is an established industrial practice for rapid prototyping and manufacturing across a range of products, components and commercial sectors and at the same time possesses great potential for every-day life applications to be invented, explored and developed by the coming generations of scientists and engineers. A 3D printer installed in a school setting and complemented by well-designed educational activities can: stimulate the interest and curiosity of students; engage and motivate them into studying science, technology, engineering and mathematics (STEM) subjects, that they may choose or consider as career options; give the opportunity to teachers to achieve content and concept learning in an innovative way. In this paper we present an interdisciplinary science course that was developed for high school students and was implemented in an actual science classroom. The objectives of the course were both to spark the interest and creativity of students and teach them certain curriculum units the content knowledge of which is reached or utilized in an unconventional way. Students are gradually introduced into the 3D printing technology, its application and potential and are assigned a challenging collaborative project in which they have to study, analyse, design and build, using the 3D printer of their school, an operational model of a renown ancient artefact, the so-called Antikythera Mechanism. The mechanism is a 2100-year-old computer and is internationally known as an artefact of unprecedented human ingenuity and scientific, historic and symbolic value. The course involves the teaching of STEM curriculum domains of physics, astronomy, mathematics/geometry, informatics and technology related content and also non-STEM subjects like history and Greek language, both ancient and modern. We give an overview of the course, discuss its various phases and highlight its outcomes.